A challenging frontier – the genomics and therapeutics of nonclear cell renal cell carcinoma. Issue 3 (May 2021) - Patel, Hiren V.; Srivastava, Arnav; Srinivasan, Ramaprasad; Singer, Eric A.
Abstract : Purpose of review: As molecular profiling of renal cell carcinoma (RCC) continues to elucidate novel targets for nonclear cell histologies, understanding the landscape of these targets is of utmost importance. In this review, we highlight the genomic landscape of nonclear cell RCC and its implications for current and future systemic therapies. Recent findings: Several genomic studies have described the mutational burden among nonclear cell histologies. These studies have highlighted the importance of MET in papillary RCC and led to several clinical trials evaluating the efficacy of MET inhibitors for papillary RCC. The success of immune checkpoint inhibitors, such as ipilimumab and nivolumab, in clear cell RCC has led to ongoing trials evaluating these novel therapeutics in nonclear cell RCC. Summary: Genomic profiling has allowed for the evaluation of novel targets for nonclear cell RCC. This evolving therapeutic landscape is being explored in promising, ongoing trials that have the potential for changing how nonclear cell RCC is managed.